Three-dimensional adiabatic quantum-flux-parametron fabricated using a double-active-layered niobium process. (9th June 2017) - Ando, Takumi; Nagasawa, Shuichi; Takeuchi, Naoki; Tsuji, Naoki; China, Fumihiro; Hidaka, Mutsuo; Yamanashi, Yuki; Yoshikawa, Nobuyuki
Abstract: Adiabatic quantum-flux-parametron (AQFP) is an ultra-low-power superconductor logic. In this study, we proposed and designed three-dimensional (3D) AQFP to achieve high circuit density and efficient interconnections. In 3D-AQFP, different AQFP logic circuits can be designed both over and under a ground plane (GP). The 3D-AQFP circuits are fabricated using the AIST 10 kA cm −2 Nb double gate process, in which two active layers are separated by a single GP. Followed by basic logic cell tests, we show an experimental demonstration of a 3D-XOR gate, the building block cells of which are vertically stacked to save circuit area and wiring length. The measurement results showed reasonable excitation current margins of more than ±16% for the 3D-XOR gate.